2015
DOI: 10.1186/s12913-015-0810-7
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated care affects hospitalization and prognosis in amyotrophic lateral sclerosis: a cohort study

Abstract: BackgroundTo determine whether an integrated approach to coordination of care influences hospitalization and clinical outcomes in a chronic neurological disease, amyotrophic lateral sclerosis.MethodsWe followed up 2452 patients with probable or definite amyotrophic lateral sclerosis from 2000 to 2012. Two cohorts were compared before and after the creation of a community care network for this disease in Ile de France in 2006. During these two periods, the medical and paramedical care teams and formal standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The median duration of hospital stay was 8 days, in line with the results of a prior Italian study (mean 10.3 days) [26] but longer than in a French study (mean 3.3 days) [13]. In the USA, the mean length of stay varied from 8.4 days [15] to 5 days [14].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The median duration of hospital stay was 8 days, in line with the results of a prior Italian study (mean 10.3 days) [26] but longer than in a French study (mean 3.3 days) [13]. In the USA, the mean length of stay varied from 8.4 days [15] to 5 days [14].…”
Section: Discussionsupporting
confidence: 77%
“…The proportion of patients hospitalized decreased from 80 % in 2000 to less than 40 % in 2012 [13]. Evaluating hospital admissions with a diagnostic code for ALS in large US administrative databases, two studies reported that emergency admissions were common while only about 20 % were elective [14, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients and their caregivers all received logistical and psychological support from the Paris ALS Network care. 16…”
Section: Methodsmentioning
confidence: 99%
“…Network care is associated with reduced hospital administration, reduced deterioration of function, and delayed mortality in patients with ALS. 18 Moreover, an integrated approach that coordinates care between the hospital and other care settings in community can influence the palliation of dying and the quality of death of patients with ALS.…”
Section: Discussionmentioning
confidence: 99%